The Effect of the Affordable Care Act Medicaid Expansion on Migration. (26th November 2016) - Goodman, Lucas
Abstract: The expansion of Medicaid to low‐income nondisabled adults is a key component of the Affordable Care Act's strategy to increase health insurance coverage, but many states have chosen not to take up the expansion. As a result, for many low‐income adults, there has been stark variation across states in access to Medicaid since the expansions took effect in 2014. This study investigates whether individuals migrate in order to gain access to these benefits. Using an empirical model in the spirit of a difference‐in‐differences, this study finds that migration from non‐expansion states to expansion states did not increase in 2014 relative to migration in the reverse direction. The estimates are sufficiently precise to rule out a migration effect that would meaningfully affect the number of enrollees in expansion states, which suggests that Medicaid expansion decisions do not impose a meaningful fiscal externality on other states.